Peritoneal Serous Papillary Adenocarcinoma: Report of Four Cases - TSUJIMURA, Takahiro; MINAMI, Takeshi; NAKATANI, Koji; KONDO, Shinya; KANAYAMA, Shuji (Internal Medicine, 2005)
We report four cases of peritoneal serous papillary adenocarcinoma (PSPC), a rare disease; all patients had ascites and high levels of serum CA125. Clinical and radiological examinations could not differentiate the disease from peritoneal metastatic tumors and mesothelioma, and histopathological analysis including immunochemistry on the specimen obtained at laparotomy or laparoscopy was necessary for the diagnosis. One patient lived for 58 months with cytoreductive surgery and chemotherapy, and another is still living after 20 months by chemotherapy alone. In patients with peritoneal tumors of unknown origin and a high level of serum CA125, taking PSPC into consideration in the differential diagnosis, histopathological examination should be performed.